Open archives for social scienceresearch in widening countries of the European Union - Schlenker, Dieter (Atlanti +, 2024)
Purpose: Archives play a key role in social sciences research by providing ac-cess to primary sources of public and private organisations, and individuals. Method/approach: A research project of archivists and scholars was launched in 2024 at the European University Institute to analyse access conditions of pub-lic archives in Widening Countries, the Western Balkans and Eastern Partner-ship Countries.Results: Two workshops were organised, one on 6 September during the Annual Graduate Conference on the history of European integration at the European University Institute, and one during the 34th International Archival Day Confer-ence organised by the International Institute of Archival Science IIAS in Maribor, Slovenia, on 26-27 November 2024. The first workshop was dedicated to a discus-sion amongst scholars of European integration history, and the latter workshop was attended by archivists of public archival institutions.Conclusion/findings: The research papers presented and discussed during the two workshops provided an up-to-date overview on legal provisions and practice in providing access to public archives in EU Widening Countries, the Western Balkans and Eastern Partnership Countries. Based on the research results and as a follow-up to the investigation, the project team intends to formulate potential elements for a training programme curriculum for archivists on the principles of access to archives in Europe.
Keywords: archives; arhivi; družboslovne raziskave; European Union; Evropska unija; odprti arhivi; open archives; social science Research